SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE ANALISIS GAP UNTUK PROSES KENAIKAN JABATAN DAN PERENCANAAN KARIR - Surya Putra, Dadang Yunika (UNIVERSITAS PELITA HARAPAN, 2017)
Fulfilling empty position on company often become complicated process because the candidate who can be placed in that position by matching between employee-profile and position-profile sometimes not well define. To minimize that problem, there should be a method such as decision support system which can analize employees who suitable with the available position. This decision support system for profile matching process and gap analization is made based on company’s data and rules which locate on JP-Insurance Jasaraharja Putra Bengkulu. Profile Matching process is taken to recommend employees in Positioning and Carrier Planning based on three stages, which are Intelectual Capacity, Working Area and Attitude. The result of this process is represented ini rank of employees as recommendation for decision maker in deciding which employee is suitable for the position.This Software is using Microsoft Access 2010 for database and Borland Delphi 7.0 as compiller. Form the result of this implementation system can be seen that this software can be very helpfull on decision support to profile matching in positioning and career planning on JP-Insurance Jasaraharja Putra Bengkulu.Keywords : System, Decision-Support , Positioning, Carrier, Information